Distribution and structure of a population of Heterotheca subaxillaris (Lam.) Britt. & Rusby (camphor weed) in La Pampa, Argentina (Semiárida, 2020)
Heterotheca subaxillaris (Lam.) Britt. & Rusby, camphorweed, is an annual weed of the Compositae family, native of United States. The aim of this work was to establish the distribution of this species in La Pampa state (Argentine), and to understand its local population dynamics through its phenological states structure. The study was carried out at two different levels: at regional level, the distribution within La Pampa, and at plot level, the phenologicals states and densities. H. subaxillaris was widely distributed in the northeast area of the state (better edaphic and climatic conditions for agriculture), and less abundant in southwest areas, mostly on sandy or sandy-loam soils. The achenes germination occurred in the fall season and growth and development was mainly in spring and summer seasons. The most sensitive phenological phase was the transition from seedling to rosette, due to a high mortality of seedlings. This phenological phase was the most prolonged and consistent with the harshest environmental conditions. The success of transition from vegetative to reproductive phase was about 25% for rosettes and 2% for seedlings.
Keywords: camphor weed; population structural; phenology; density